ASSESSING STUDENT WRITING IN EFL CLASSES BY USING AFL - Mamura Alimova, Mamura Alimova (Журнал иностранных языков и лингвистики, 2021)
This article deals with the issue of assessing student writing in EFL classes by using assessment for learning (Afl) and reflect writing teachers’ assessment.